2017
DOI: 10.1093/nar/gkx044
|View full text |Cite
|
Sign up to set email alerts
|

RNA binding and chaperone activity of theE. colicold-shock protein CspA

Abstract: Ensuring the correct folding of RNA molecules in the cell is of major importance for a large variety of biological functions. Therefore, chaperone proteins that assist RNA in adopting their functionally active states are abundant in all living organisms. An important feature of RNA chaperone proteins is that they do not require an external energy source to perform their activity, and that they interact transiently and non-specifically with their RNA targets. So far, little is known about the mechanistic detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 42 publications
2
60
0
Order By: Relevance
“…Rennella et al used time-resolved NMR spectroscopy to observe how multiple CspA proteins facilitate the dimerization of two complementary RNA hairpins (82). The slowest unfolding rate equaled the rate of RNA dimerization, suggesting that each hairpin must unzip before the two strands can anneal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rennella et al used time-resolved NMR spectroscopy to observe how multiple CspA proteins facilitate the dimerization of two complementary RNA hairpins (82). The slowest unfolding rate equaled the rate of RNA dimerization, suggesting that each hairpin must unzip before the two strands can anneal.…”
Section: Introductionmentioning
confidence: 99%
“…This combination of aromatic and basic side chains, found in other RNA binding proteins (83), seems to offer a flexible yet energetically favorable interaction surface for single-stranded RNA. Importantly, side chains on the exposed surface of CspA are dynamic (84), but are stabilized upon binding to the RNA hairpin (82). Thus, increased motion in the RNA base pairs is accompanied by reduced motion in the protein.…”
Section: Introductionmentioning
confidence: 99%
“…As the structure of CspA has been characterized by X-ray diffraction and nuclear magnetic resonance spectroscopy (Schindelin et al, 1994; Newkirk et al, 1994), we used the CspA structure (PDB ID: 1MJC) as a template to predict that the structure of CspL was also a β-barrel comprising four flexible loops between five β-sheets that act as linkers to form a hollow structure (Figure 4A). As CspA is known to bind RNA molecules (Giuliodori et al, 2010; Rennella et al, 2017), this structural similarity suggested that CspL may function as an mRNA chaperone to confer the growth- and biomass accumulation-promoting effects that we observed in E. coli .…”
Section: Resultsmentioning
confidence: 56%
“…The aromatic residues present within the RNA‐binding motifs of CSPs, RNAP1 and RNAP2, enable interactions with the RNA chain (Lee et al, ; Newkirk et al, ). Several studies showed how mutating residues from the aromatic cluster of E. coli CspA and B. subtilis CspB impaired their nucleic acid‐binding capacity (Hillier, Rodriguez, & Gregoret, ; Rennella et al, ; Schröder, Graumann, Schnuchel, Holak, & Marahiel, ). Additional works on the structural features of this protein domain revealed key amino acids involved in the protein‐nucleic acid interaction.…”
Section: Introductionmentioning
confidence: 99%